1997
DOI: 10.1200/jco.1997.15.4.1502
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic evaluation of the topoisomerase inhibitor irinotecan in cancer patients.

Abstract: The high degree of interpatient variability in parameter estimates suggests pharmacogenetic variation or differential induction or inhibition of the sequential metabolic pathway of CPT-11, as well as variability in transport systems. The low urinary recovery indicates substantial biliary excretion and supports the significant correlation between intestinal toxicity and BI. Black patients are not at increased risk of toxicity. An assessment of individual differences in SN-38 conjugation remains to be establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 32 publications
6
93
1
2
Order By: Relevance
“…␤-Actin cDNA was labeled using random primers with [␣-32 P]CTP (3,000 Ci/mM). In Situ Hybridization-In situ hybridization to mRNA was carried out with each unique 5Ј region (from nucleotide 1 to 320) that contains from 10 to 26% differences between UGT1A7 through UGT1A10 cDNAs for sense or antisense riboprobe labeled with [␣- 35 S]CTP (1500 Ci/mM). Riboprobes were alkali-hydrolyzed generating, on average, 100 -200-nucleotide hybridizing fragments and washed under high stringency at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…␤-Actin cDNA was labeled using random primers with [␣-32 P]CTP (3,000 Ci/mM). In Situ Hybridization-In situ hybridization to mRNA was carried out with each unique 5Ј region (from nucleotide 1 to 320) that contains from 10 to 26% differences between UGT1A7 through UGT1A10 cDNAs for sense or antisense riboprobe labeled with [␣- 35 S]CTP (1500 Ci/mM). Riboprobes were alkali-hydrolyzed generating, on average, 100 -200-nucleotide hybridizing fragments and washed under high stringency at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] While the primary selective pressure for UGT1A enzyme function may have been metabolism of endogenous molecules, UGT1A function is necessary for elimination of exogenous compounds such as the anti-cancer drug irinotecan. [16][17][18] The same common UGT1A1 variants associated with mild elevations of serum bilirubin are associated with diminished in vitro glucuronidation of the active irinotecan metabolite, SN-38, [19][20][21][22] and prolonged exposure and increased toxicity in patients receiving this agent. [23][24][25] As shown by Sai et al, 25 re-sequencing of the UGT1A1 gene in 85 Japanese patients treated with irinotecan confirmed that the haplotypes containing lower expression variants were associated with both a low SN-38G/SN-38 AUC ratio and elevated pretreatment bilirubin concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the feasibility and interest of higher doses of irinotecan in patients as monotherapy (7,14) or in combination with 5FU: FOLFIRI regimen (8). The important interpatient variability for irinotecan pharmacokinetic can be, at least partly, explained by the UGT1A1 Ã 28 polymorphism (15).…”
Section: Discussionmentioning
confidence: 99%